Pengaruh Leverage, Ukuran Perusahaan, Profitabilitas, Kualitas Audit, dan Komite Audit terhadap Manajemen Laba - Nimas Arum Sari; Yeye Susilowati (Jurnal Ilmiah Aset, 2021)
This test is conducted in order to analyze and test the leverage, company size, profitability, and audit quality, and the audit committee in influencing earnings management. This research is sourced from an annual report from a manufacturing company on the Indonesia Stock Exchange. Starting from 2015 to 2018. Samples taken by researchers there are certain criteria in order to obtain more representative data. So that a total sample of 327 manufacturing companies was obtained during the study period. Researchers used secondary data, the data obtained through the site www.idx.co.id, www.sahamok.com, and several related company websites. This data analysis tool uses multiple linear regression. The end of this test includes evidence in the form of leverage and audit committee which has a positive and significant effect on earnings management, while company size, profitability and audit quality have no effect on earnings management.